Assessing SSR Relative Data Capacity - Обод, І. І.; Свид, І. В.; Заволодько, Г. Е.; Мальцев, О. С.; Бакуменко, Б. В.; Чумак, В. С. (UKRCON, 2021)
Secondary Surveillance Radars are widely used in many aspects of users’ information support, such as air object recognition and radio beacon tracking. The study considers a two-channel data transmission system as an SSR model and assesses its relative data capacity subject to intentional (correlated and uncorrelated) and intra-system interference as well as fluctuation (masking effect) noise in the request and response channels. It is shown that the aircraft transponder design built on the principles of a single-channel queuing system with denial of service has a significant impact on Secondary Surveillance Radar relative data capacity and the information security of both the aircraft transponder and the entire Secondary Surveillance Radar.
Keywords: secondary surveillance radar; air traffic control; air object; aircraft transponder; cooperative surveillance systems; intra-system interference; identification friend or foe; information support